Future reform of Chinese elite sport management system : perspective of sport events - Jiang, Xiaotian (2010)
The primary intention of this study is to present and evaluate the elite sport management system in China and to predict the trend of future reformation in Chinese elite sport management system. In addition, this study attempts to enhance the understanding to Chinese sport management system.